2019
DOI: 10.1097/bot.0000000000001391
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Analgesia Approach to Fragility Hip Fracture: A Single-Center, Retrospective, Cohort Study on Femoral Nerve Block

Abstract: Objective: To determine whether an effective opioid-sparing pain control modality is desirable for an aging population. Design: Retrospective observational study Setting: Academic medical center Patients: 192 patients with various types of fragility hip fractures Intervention: A single-injection femoral nerve block (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…They also found a significant decrease in opioid use and pain (as measured by VAS-score). [ 24 ] This is similar to our results.…”
Section: Discussionsupporting
confidence: 93%
“…They also found a significant decrease in opioid use and pain (as measured by VAS-score). [ 24 ] This is similar to our results.…”
Section: Discussionsupporting
confidence: 93%
“…Due to various advantages, such as better comfort and safety, higher patient satisfaction, shorter hospitalization and less hospitalization cost, ultrasound-guided peripheral nerve blocks (PNB) has gained increasing popularity among anesthesiologists and patients [ 12 – 14 ]. Both prospective or retrospective studies and meta-analysis have consistently confirmed that peripheral nerve block has fewer unwanted effects on cardiopulmonary function, as well as significantly fewer related complications, as compared with other anesthesia methods [ 15 17 ]. Because of the particularity of the sciatic nerve, anesthesiologists can perform sciatic nerve block at many parts of the body surface, such as superior sciatic block, popliteal block and ankle joint block.…”
Section: Introductionmentioning
confidence: 99%
“…Patients receiving the hip blockade less than 4 hours before surgery were excluded from the study. A singleshot nerve block is demonstrated to be effective as preoperative analgesia for hip fracture patients, reduces the needs for opioids before surgery and decreases postoperative delirium ( 24 , 25 ). The use of preoperative femoral hip blockade alone has, however, not shown a reduction in postoperative opioid consumption ( 25 ).…”
Section: Discussionmentioning
confidence: 99%